2008
DOI: 10.1104/pp.108.116004
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression and Metabolism in Tomato Fruit Surface Tissues    

Abstract: The cuticle, covering the surface of all primary plant organs, plays important roles in plant development and protection against the biotic and abiotic environment. In contrast to vegetative organs, very little molecular information has been obtained regarding the surfaces of reproductive organs such as fleshy fruit. To broaden our knowledge related to fruit surface, comparative transcriptome and metabolome analyses were carried out on peel and flesh tissues during tomato (Solanum lycopersicum) fruit developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
326
4
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(350 citation statements)
references
References 114 publications
17
326
4
1
Order By: Relevance
“…Because pericarp thickness did not differ between wild-type and transgenic tomatoes, we investigated if altered epidermis characteristics could explain the increased water loss. The epidermal cell layer is the outermost layer of the fruit pericarp and is covered by a waxy cuticle that thickens as the fruit ages, protecting the fruit from desiccation (Mintz-Oron et al, 2008). The thickness of the waxy cuticle can be determined with Sudan staining, which has a high affinity for lipids.…”
Section: Ful1/2 Silenced Fruits Show Normal Pericarp Development Butmentioning
confidence: 99%
See 1 more Smart Citation
“…Because pericarp thickness did not differ between wild-type and transgenic tomatoes, we investigated if altered epidermis characteristics could explain the increased water loss. The epidermal cell layer is the outermost layer of the fruit pericarp and is covered by a waxy cuticle that thickens as the fruit ages, protecting the fruit from desiccation (Mintz-Oron et al, 2008). The thickness of the waxy cuticle can be determined with Sudan staining, which has a high affinity for lipids.…”
Section: Ful1/2 Silenced Fruits Show Normal Pericarp Development Butmentioning
confidence: 99%
“…The cuticle has been reported to be an important transpiration barrier (Mintz-Oron et al, 2008); therefore, the altered expression of fatty acid biosynthesis genes may contribute to the increased water loss of the FUL1/2 silenced fruits. We found several genes related to cutin and fatty acid synthesis to be downregulated in FUL1/2 silenced fruits, among which were a glycerol-3-Pacyltransferase (log 2 = 21.2) and a cytochrome P450 hydroperoxide lyase (HPL) (log 2 = 21.8).…”
Section: Transcriptome Analysis Suggests Altered Lipid And/or Cuticlementioning
confidence: 99%
“…The plasma membrane ATP-binding cassette transporters have been implicated in the transport of both wax and cutin to the apoplast, whereas lipid transfer proteins very likely contribute to the transport of cutin monomers through the cell wall to the cutin layer (Yeats and Rose, 2013). The implication of enzymes of the GDSL lipase family in cutin assembly, which is long suspected (Reina et al, 2007;Mintz-Oron et al, 2008), was recently demonstrated in tomato (Solanum lycopersicum; Girard et al, 2012;Yeats et al, 2012a).…”
mentioning
confidence: 99%
“…Both the nutritional and the sensorial attributes are built throughout the successive phases of fruit development, namely cell division, cell expansion, and ripening. While the fruitripening process is obviously important (Giovannoni, 2001), there is also a growing body of evidence that supports the key role of early fruit development for the acquisition of several fruit quality traits, including the accumulation of sugars and organic acids (Guillet et al, 2002;Lemaire-Chamley et al, 2005;Petreikov et al, 2006), the determination of cell wall and texture characteristics (Chaïb et al, 2007), and the cuticle biosynthesis (Mintz-Oron et al, 2008). In the growing fruit, these processes mainly take place during the cell expansion phase, which sustains fruit growth by allowing a large increase in fruit cell volume linked with membrane and cell wall/synthesis and the con-comitant accumulation of water, mineral ions, and metabolites in the vacuoles, thereby conferring its fleshy characteristics to the fruit.…”
mentioning
confidence: 99%
“…Coexpression analyses allowed the identification of genes regulating tissue and cell development (Persson et al, 2005;Gifford et al, 2008), environmental responses , and plant metabolism Gutiérrez et al, 2008) and were further validated by reverse genetics strategies. With the current availability of large-scale gene expression and metabolite profiling techniques in many plants, including tomato (Alba et al, 2004(Alba et al, , 2005Lemaire-Chamley et al, 2005;Moco et al, 2006;Mounet et al, 2007;Saito et al, 2007;Mintz-Oron et al, 2008;Schauer et al, 2008), large gene expression and metabolite data sets can be combined through correlation and clustering analyses (Urbanczyk-Wochniak et al, 2003) and further represented as a network of relationships between genes and metabolites Saito et al, 2007;Hoefgen and Nikiforova, 2008). These approaches have been successfully applied to the discovery of regulatory and biosynthetic genes involved in the control of metabolite production, such as the glucosinolate metabolism (Hirai et al, 2004.…”
mentioning
confidence: 99%